Examining local government expenditures on entrepreneurship development in Tanzania: A case of Mbinga district. - Ntandu, Christopher Robert (Mzumbe University, 2026)
A dissertation submitted in partial fulfilment of the requirements for an award of the of Masters of Science in Project Planning and Management (Msc.PPM) of Mzumbe University